TRAINING OF FUTURE SPECIALISTS FOR THE FORMATION OF THE NATIONAL-LINGUISTIC PERSONALITY OF THE PRE-SCHOOL CHILD - Ковшар, Олена (SWorldJournal, 2023)
In accordance with the requirements of social order of the state, one of leading tasks to modernisation of education is forming of Ukrainian nationally conscious language personality that is marked the high culture of commonunication, by the realized atti